Hypoxia and Inflammation: Insights From High-Altitude Physiology - Pham, Kathy; Parikh, Keval; Heinrich, Erica C. (Frontiers in Physiology, 2021)
The key regulators of the transcriptional response to hypoxia and inflammation (hypoxia inducible factor, HIF, and nuclear factor-kappa B, NF-κB, respectively) are evolutionarily conserved and share significant crosstalk. Tissues often experience hypoxia and inflammation concurrently at the site of infection or injury due to fluid retention and immune cell recruitment that ultimately reduces the rate of oxygen delivery to tissues. Inflammation can induce activity of HIF-pathway genes, and hypoxia may modulate inflammatory signaling. While it is clear that these molecular pathways function in concert, the physiological consequences of hypoxia-induced inflammation and how hypoxia modulates inflammatory signaling and immune function are not well established. In this review, we summarize known mechanisms of HIF and NF-κB crosstalk and highlight the physiological consequences that can arise from maladaptive hypoxia-induced inflammation. Finally, we discuss what can be learned about adaptive regulation of inflammation under chronic hypoxia by examining adaptive and maladaptive inflammatory phenotypes observed in human populations at high altitude. We aim to provide insight into the time domains of hypoxia-induced inflammation and highlight the importance of hypoxia-induced inflammatory sensitization in immune function, pathologies, and environmental adaptation.